2014
DOI: 10.1007/s11010-014-2281-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-135b promotes proliferation and invasion of osteosarcoma cells via targeting FOXO1

Abstract: Recent data strongly suggest the important role of miRNAs in various cancer-related processes. Osteosarcoma (OS) is the most common primary cancer of the bone and usually leads to deaths due to its rapid proliferation and metastasis. Here, we demonstrated that compared with noncancerous bone tissues, miR-135b expression is frequently upregulated in OS specimens, inversely correlated with potential target-FOXO1 expression pattern. Bioinformatics analysis combined with experimental confirmation revealed FOXO1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…MiRNA expression and biological function have been studied in various tumors. MiRNA microarrays have clarified their relationship with tumor occurrence, development, and differentiation, and in favor of tumor diagnosis and classification Pei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA expression and biological function have been studied in various tumors. MiRNA microarrays have clarified their relationship with tumor occurrence, development, and differentiation, and in favor of tumor diagnosis and classification Pei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] With the improvements of osteosarcoma therapeutic strategies including adjuvant chemotherapy, radiotherapy and wide tumour excision, the 5-year survival rate of osteosarcoma cases without metastatic disease is improved to 65%. [6][7][8][9] However, a half of patients will develop metastases and few of these patients could be cured.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that hyperactivation of the Notch or Wnt/β-catenin pathways in tumors is partly associated with the dysregulation of certain microRNAs (miRNAs) that in turn regulate the Notch or Wnt/β-catenin pathways 23, 24. Aberrantly regulated expression of miR-135b has been detected in several types of tumors including OS 25, 26. Interestingly, although not in tumors, upregulated miR-135b results in the activation of Wnt/β-catenin signaling in glomerulopathies 27 .…”
Section: Introductionmentioning
confidence: 99%